Consolidation of Disability Groups in Fighting for "Right to City" in Surakarta City - Wandy Wiguna, Ringgana; Utami, Trisni; Ramdhon, Akhmad (International Journal of Educational Research & Social Sciences, 2023)
A city is a spatial space in which there are many groups of individuals who gather with each other by relying on social relations. As a social space, the city evokes a lot of activity in it. In this perspective, the social space explains that disputes, consensuses, negotiations, and conflicts ultimately occur in the city space due to the power relations of the actors in it. One of the actors who play the role is the disabled group. They are within the city and have the right to be able to feel everything that is provided within the city. Accessibility difficulties for some community groups including people with disabilities. This is important to discuss because people with disabilities are also part of society. They have the right to use public facilities and public security, which the state must provide for them. The purpose of this study is to look at the consolidation of disabled groups in defending the right to cities. The result of this research is that disabled groups can communicate between institutions and communities with the Surakarta government. They succeeded in pushing several policies and trustees until they were included in the formulation of programs from existing Government Organizations.